Higher education institutions in Algeria and their role in supporting innovation and entrepreneurship - Fatiha Safi; Fatiha Beldjilali (Dirassat Journal Economic Issue, 2024)
The study seeks to identify the extent to which higher education institutions contribute to supporting innovation, entrepreneurship and the creation of pilot projects, as well as showing the strategies adopted by the Algerian state to make these institutions a springboard for creativity.Innovation and Ministerial Resolution 1275 as the most important. The results concluded that this decision created a dynamism in the midst of higher education institutions and was welcomed by professors and students, so that hundreds of notes were prepared within its framework and dozens of them were discussed, and hundreds of them are still in the process of being completed. The memorandum that will be transformed into a start-up, especially since the time allotted for this is a few months and give an opportunity for students of other years to put forward their ideas and involve them in preparing entrepreneurial projects through research and business plans.